O ambiente de potencial formação (APF) como mediação para a acessibilidade de estudantes com deficiência na educação superior a distância - Dillenburg, Andreia Ines (2021)
This research was carried out in the Postgraduate Program in Education-PPGE/UFSM, PhD course. The objective was to analyze the contributions of a training process with tutors / teachers with a view to raising the accessibility of students with disabilities in distance education. With specific objectives, we seek to present the theoretical possibilities of special education, through training that aims to share with teachers and tutors theoretical reflections, actions and resources that raise the accessibility of students with disabilities. As well as seeking to promote accessibility issues in distance education, providing tools and support for the actions and resources of Higher Distance Education. Finally, check the methodological possibilities of accessibility on the Moodle platform. The methodological approach is of a qualitative nature, adopting the operational aspects of Intervention research, following the definition of Damiani et al. (2013). The research of the intervention type has as its base plan the Historical Cultural Activity Theory, in the version developed by Yrjö Engeström. Its operation took place through semi-presential training in the Potential Training Environment (APF), which is based on the concepts developed by the Learning Laboratory of Engeström (2009). Data collection took place through interviews, before and after training with students, specialized tutors and distance tutors. The analysis of the data obtained occurred through the Content Analysis technique, based on Bardin (2008), and was divided into two major categories, the first of which is directed to the influence of the reserve of places and the entrance of students with disabilities in higher education. The second is more directly related to the perspectives, formulations and possibilities experienced in the formation of the APF. The results show that the formation of the APF aimed to provide the expansion of the object of activity by the teachers, through mediation on the accessibility of students targeted by special education in distance education. It should be noted that the influences of a formative process for accessibility were noticeable in the speech and / or in the teaching practices that participated in the formation of the APF. Being able to transcend the activity systems for which they were conceived and pass on impacts to other historical and social places that these subjects experience. It can be seen that the APF can provide improvements in the conditions of permanence and the promotion of learning by students targeting special education, with more equity. Thus, the results indicate that the formative processes for accessibility, along the lines of the APF, are potential mediators for the expansion of awareness and instrumental activity (use of signs and tools), directly influencing training participants and indirectly, but collectively, its students special education public.